Carta de Adolfo Porrata Doria a Beningo Fernández García - Todd, Roberto H.; Porrata Doria, Adolfo; Fernández García, Benigno (My University, 1935)
Situación de la viuda e hijos de Manuel A. Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934